PENGARUH PEMANFAATAN MEDIA INTERNET DAN MEDIA VCD TERHADAP PRESTASI BELAJAR SISWA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL EKONOMI DITINJAU DARIMOTIVASI BELAJAR - Rony Arpinto Ady; Soetarno Joyoatmojo; Guntur Riyanto (Universitas Sebelas Maret Surakarta, 2014)
Background: The aims of this research are to know: (1) The difference of effect between internet media and VCD media to the achievement in social science of economics , (2) The difference of effect between high learning motivation and low learning motivation to the achievement in social science of economics, (3) The effect interaction between learning media and students' learning motivation to the achievement in social science of economics. Subjects and Methods: The kind of research used in this study is experiment. The population of the research is the students of junior high school at the Islamic Foundation in Kartasura and Gatak District. All of the samples were taken by using a multi-stage cluster random sampling technique. The sample is 127 students represent the population of 771 students. The data of the research were gathered by using questionnaire for learning motivation and test for learning achievement. The data were analyzed by a two-way analysis of variance.Results and Conclusion:(1) There was significant effect difference between internet media and VCD media to the achievement in social science of economics (Fobs: 243.86 > Ftable: 3.84), (2) there was significant effect difference between high learning motivation and low learning motivation toward achievement in social science of economic between students who have high motivation to students who have low motivation (Fobs: 27.526> Ftable: 3.84 ), (3) there was effect interaction between learning media and learning motivation for achievement social science of economics (Fobs: 6.396 > F table: 3.84). All of at significance level of 0.05.